KAJIAN PENGELOLAAN TAMAN WISATA ALAM WERA DI KABUPATEN SIGI PROVINSI SULAWESI TENGAH - La’bi, Semuel Taruk (JSTT, 2014)
Wera Natural Tourism Site and its surroundings which have its beauty of waterfall and environment have not directly benefited the community’s economy. The purpose of this research was to investigate the social, economic and ecological aspects of the management of Wera Natural Tourism Site, to analyze the problem of managing the site, and to provide strategies for managing the site. This research was conducted in Balumpewa, Sigi Regency, Central Sulawesi in the middle of July to September 2013. The primary and secondary data were obtained through interviews with 30 respondents and 10 key informants; observation, and library research. The data were analyzed descriptively and SWOT analysis. The research indicates that in general the villagers in Balumpewa had positive motivation and perceptions on Wera Natural Tourism Site as supporting forest and natural tourism. Economically, the villagers only rely on the crops of both forest and agriculture. Few villagers have taken benefits from the natural tourism site also has ecological function in preventing erosion and flooding, in forming micro climate, and providing macro habitat and other micro agranims. The main strategy that needs to be taken is to promote and maximize the water environment to support the economy, the third party investment, and the community’s participation together with the forest police in preventing the forest. Alternatively, other strategies are to manage the boundary between forest area and farming, to get the village chief in providing job opportunities, to increase the structure and infrastructure, and to get the community’s in protecting and conserving not only the forest, but also the safety of the visitors.